Review on Collagen as a wound healer. - G.S, Tribhuvan; B, Velhal A; D, Jadhav. P; K, Redasani V (Asian Journal of Pharmaceutical Research and Development, 2022)
In reaction to the tissue injury, normal wound healing process goes through inflammatory, proliferative, and remodeling stages. Impairments any one of these stages cause the wound to become chronic and non-healing, necessitating intervention to bring returning the process to its original state. Collagen, a fundamental has a role in the matrix extracellular an important function in wound healing regulation, whether in its native fibrillar form or in the wound as soluble components environment. Collagen has been used as an additional wound treatment to aid healing since it is involved in the control a combination of a few of these processes. The importance of collagen in various biological processes related to wound healing is discussed in this paper, additionally to a survey of the existing research in regards to the utilization of collagen-based wound care. There are several techniques to developing recommendations, but no gold standard has emerged so till now.